Hello beautiful : a novel - Napolitano, Ann (The Dial Press, 2024)
"William Waters grew up in a house silenced by tragedy, where his parents could hardly bear to look at him, much less love him. So it's a relief when his skill on the basketball court earns him a scholarship to college, far away from his childhood home. He soon meets Julia Padavano, a spirited and ambitious young woman who surprises William with her appreciation of his quiet steadiness. With Julia comes her family; she is inseparable from her three younger sisters: Sylvie, the dreamer, is happiest with her nose in a book and imagines a future different from the expected path of wife and mother; Cecelia, the family's artist; and Emeline, who patiently takes care of all of them. Happily, the Padavanos fold Julia's new boyfriend into their loving, chaotic household. But then darkness from William's past surfaces, jeopardizing not only Julia's carefully orchestrated plans for their future, but the sisters' unshakeable loyalty to one another. The result is a catastrophic family rift that changes their lives for generations. Will the loyalty that once rooted them be strong enough to draw them back together when it matters most?"--